The discovery of the genus Protodacnusa Griffiths, 1964 (Hymenoptera: Braconidae, Alysiinae) in China, with descriptions of six new species - Mao, Juan; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2015)
The genus Protodacnusa Griffiths, 1964 (Braconidae: Alysiinae: Dacnusini) is newly recorded from China with six new species being described, namely Protodacnusa defectivus sp. nov., P. dimorphus sp. nov., P. helanensis sp. nov., P. longicaudatus sp. nov., P. magnidentis sp. nov. and P. nigra sp. nov. A key to the species of Protodacnusa worldwide is provided.